Kritik Etika Diskursus Habermas terhadap Praktik Manipulasi Komersial Buzzer dan Influencer di Ruang Publik Digital - Dicky Mardona (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The expansion of social media has transformed the digital public sphere into a space increasingly influenced by commercial interests and information manipulation. The growing presence of buzzers and influencers has contributed to the spread of misleading narratives, hidden advertising practices, and opinion engineering that potentially weaken rational public communication. This study aims to examine these phenomena through Jürgen Habermas’s discourse ethics, particularly the concepts of communicative action, validity claims, and the colonisation of the lifeworld. The research employs a qualitative approach using critical philosophical analysis of digital communication practices discussed in contemporary academic literature and public discourse. The findings indicate that the communication practices carried out by buzzers and influencers tend to reflect strategic action rather than communicative action because messages are often designed to achieve economic or political objectives instead of mutual understanding. Such practices violate the principles of truthfulness, sincerity, and appropriateness within public communication. Furthermore, the commercialisation of online interaction gradually shifts social relationships into instrumental relations shaped by market logic. This condition highlights the importance of strengthening digital literacy and ethical awareness to support a healthier and more democratic digital public sphere.